Gambaran Pengetahuan Ibu Tentang Pertolongan Pertama Luka Bakar di Klinik Romana Tanjung Anom Tahun 2024 - Peterman Jaya Mendrofa; Rusmauli Lumban Gaol; Nasipta Ginting (NAJ Nursing Applied Journal, 2024)
Burns are the destruction or death of tissue that occurs when tissue comes into contact with heat. Burned skin causes damage to the epidermis, dermis, and tissue lining under the skin on the causative factors and length of contact with heat sources. These burns are caused by human activities every day, whether in family work, companies, traffic accidents, or natural disasters. The purpose of this study is to find out an overview of the level of knowledge of mothers about first aid. This type of research uses a descriptive design, and sampling in this study uses an accidental sample with a total of 58 respondents. It can be concluded that this study obtained results from Definitions in the good category of 52 respondents (89.7%), as well as Etiology in the good category of 29 respondents (50.0%), and Implementation as many as 40 respondents (69.0%). It is hoped that with the increase in maternal knowledge about burns, nurses need to provide education and counseling to the community so that the level of maternal knowledge about burns can increase at the Romana Tanjung Anom Clinic 2024.